(untitled) (Research, Society and Development, 2022)
Cancer is the second leading cause of death in the world, after cardiovascular diseases. In the USA, around 153,000 and more than 169,000 deaths were estimated for gastrointestinal tract (GIT) cancers in 2016 and 2021, respectively, while in Brazil there were more than 81,000 deaths from the same type of cancer in 2021. However, literature regarding estimates for cancer in the interior of the State of Goias is scarce. Thus, the aim of this work was to evaluate the incidence of GIT cancer in the city of Itumbiara. Possible risk factors for the more incident types of GIT cancer in the city were searched, to provide scientific data, guide and recommend public policies to managers. After approval by the Research Ethics Committee of the University, data were retrospectively collected from 525 patients treated between 1999 and 2019 at the Support Center for Cancer Carriers in Itumbiara (NAPCI), of which 85 were diagnosed with GIT cancer. The results show that the age group of 45-53 years was the most frequent (29.76%) and 2010 was the year with the highest incidence (9). Colorectal cancer was the most prevalent (46 cases: 54.76%), followed by stomach (17 cases: 20.24%), and oral cavity (6 cases: 9.52%). We conclude that local and regional epidemiological research like this one is important to contribute to monitoring and recommending health managers better strategies for screening, early detection and prevention against various types of GIT cancer in small towns.